Vestibular schwannoma: 825 cases from a 25-year experience - Pinna, Mariana Hausen; Bento, Ricardo Ferreira; Neto, Rubens Vuono de Brito (International Archives of Otorhinolaryngology, 2012)
Introduction: Acoustic nerve tumors have been recognized as a clinico-pathologic entity for at least 200 years, and they represent 90% of cerebellopontine angle diseases. Histologically, the tumors are derived from Schwann cells of the myelin sheath, with smaller tumors consisting of elongated palisade cells, while in large tumors, cystic degeneration can be found in the central areas, possibly due to deficient vascularization. We retrospectively reviewed 825 cases of vestibular schwannomas, reported between January 1984 and August 2006, in which the patients underwent surgery to remove the tumor.Objective: To evaluate signs, symptoms, aspects of clinical diagnosis, including the results of audiological and imaging studies, and surgical techniques and complications.Methods: A retrospective chart review. The medical records of all patients undergoing surgical treatment for schwannoma during the period indicated were reviewed.Results and Conclusion: Hearing loss was the first symptom reported in almost all cases, and tumor size was not proportional to the impairment of the auditory threshold. The surgical techniques allowed safe preservation of facial function. In particular, the retrolabyrinthine route proved useful in small tumors, with 50% preservation of hearing.
Keywords: neuroma; acoustic; vestibulocochlear nerve diseases; cranial nerve neoplasms